The Role of the Yelfi Salon Course and Training Institute (LKP) in Community Empowerment in Kampal Village, Parigi District, Parigi Moutong District - Yelfi Yelfi; Moh. Asri Hente; Fitriani Ayuningtias (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
This study aims to describe/describe: 1) the role of LKP Yelfi Salon in empowering the people of Kampal Village 2) knowing the empowerment process that LKP Yelfi Salon has carried out of Kampal Village. This research is a descriptive study with a qualitative approach. The research subjects were all of LKP Yelfi Salon's management, totaling seven people consisting of 4 administrators and three instructors. This research was conducted from April to May 2020. The data collection techniques used were: 1) interviews, 2) observation, and 3) documentation. While the research instruments used were interview guidelines, observation sheets, and documentation. The data analysis technique used was data reduction, data presentation, and verification of conclusions, data sources. Triangulation is carried out to explain the validity of the data using sources. The results showed that the empowerment to improve the standard of living and community skills carried out by LKP Yelfi Salon through hair beauty course activities was carried out well. In its implementation, through an approach to the community, showing problems, providing problem-solving, showing the importance of change, implementing empowerment, until the assistance supplied by LKP Yelfi Salon can help the organization to rise and improve their standard of living and their families, and make the community able to live independently. Communities are also formed to be more aware of the surrounding environment. They can take advantage of the opportunities around them while continuing to hone the skills they already have.